THE PROBLEM OF THE NEGATIVE IMPACT OF GADGETS ON THE HEALTH OF YOUNG CHILDREN AND METHODS OF THEIR SOLUTION - Elena Mikhaelovna Ljubimova; Urinbaeva Azada Bakhadirovna (Galaxy International Interdisciplinary Research Journal, 2024)
This article examines the multifaceted impact of gadgets on the health and development of young children, emphasizing both the benefits and risks associated with their use. It highlights research indicating that while interactive educational applications can support cognitive development, excessive screen time may impede speech, language, and emotional development. The detrimental effects on sleep quality and physical health, such as vision problems and reduced physical activity, are also discussed.